The Effects of Explicit Grammar Instruction on the Learning of Simple and Complex Grammar Rules - BELKACEM-BOURICHA, Karima (Journal of Human Sciences, 2015)
This study examines the effects of explicit instruction on learning simple and complex rules. While the target simple rule underlies the optional inversion of subject and verb following fronting of adverb of place, the two target complex rules underlie the formation of pseudo-cleft sentences headed by ‘where’ and ‘what’. Difference in the instructional condition depends on the presence or absence of explicit grammatical information. The results indicate that subjects in the explicit grammar condition outperformed the subjects in the implicit condition in both the simple and complex rules. These results support previous findings that explicit instruction leads to gains in learning second / foreign language grammatical items.